Measure Neutral Functional Differential Equations as Generalized ODEs - Federson, M.; Frasson, M.; Mesquita, J. G.; Tacuri, P. H. [UNESP] (Springer, 2019)
In this paper, we introduce a class of measure neutral functional differential equations of type through the relation with a certain class of eneralized ordinary differential equations introduced in Federson and Schwabik (Differ Integral Equ 19(11):1201-1234, 2006) (we write generalized ODEs), using similar ideas to those of Federson et al. (J Differ Equ 252(6):3816-3847, 2012). By means of the correspondence with generalized ODEs, we state results on the existence, uniqueness and continuous dependences of solutions for our equation of neutral type.
Keywords: Generalized ordinary differential equations; Neutral measure functional differential equations; Kurzweil-Henstock-Stieltjes integral